2015
DOI: 10.1007/s11032-015-0345-y
|View full text |Cite
|
Sign up to set email alerts
|

Two quantitative trait loci for grain yield and plant height on chromosome 3 are tightly linked in coupling phase in rice

Abstract: Plant height is a very important trait affecting rice production. The introduction of the Green Revolution gene, sd-1, into rice cultivars to create semi-dwarfism has increased grain production. In the development of modern rice breeding, there is an urgent need for a somewhat higher plant for not only maintenance of strong lodging resistance, but also more biomass. In this study, the plant height quantitative trait locus (QTL) qPH3 with moderate effect and the yield per plant QTL qYD3 were identified on chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Neighbouring QTL that are linked in coupling phase are commonly observed in primary QTL analysis (Fan et al 2017; Wu et al 2015). To date, many studies have tried to dissect QTL in coupling phase using NILs or residual heterozygous lines and found that coupling QTL were partially attributed to tightly linked independent QTL (Chemayek et al 2017; Shen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neighbouring QTL that are linked in coupling phase are commonly observed in primary QTL analysis (Fan et al 2017; Wu et al 2015). To date, many studies have tried to dissect QTL in coupling phase using NILs or residual heterozygous lines and found that coupling QTL were partially attributed to tightly linked independent QTL (Chemayek et al 2017; Shen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have tried to dissect QTL in coupling phase using NILs or residual heterozygous lines and found that coupling QTL were partially attributed to tightly linked independent QTL (Chemayek et al 2017; Shen et al 2011). For example, Wu et al dissected two tightly linked QTL for PHT ( qPH3 ) and yield per plant ( qYD3 ) by using two rice near isogenic populations (Wu et al 2015). In wheat, tight repulsion linkage between Sr36 and Sr39 was revealed by genetic, cytogenetic and molecular analyses (Chemayek et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Such a procedure is easy to implement and very cheap in computation as compared to the methods by permuting the original individual-level data in the hotspot analysis (see The permutation algorithm ) . It has been observed that QTL or genes for genetically correlated traits have a tendency to cluster on the same or adjacent regions of chromosomes in several organisms, which may be due to linkage, pleiotropy or natural selection for co-adapted traits (Studer and Doebley 2011; Wu et al 2015). The grouping strategy attempts to take the clustering phenomenon into account in the detection of QTL hotspots.…”
Section: Discussionmentioning
confidence: 99%
“…Clustering of QTLs for genetically correlated traits in the same or adjacent regions of HGs in several organisms may be due to physical linkage, pleiotropy or natural selection for coadapted traits (Studer and Doebley, 2011;Wu et al, 2015). We have taken the first step in the identification of loci that lead to these trait correlations and the degree to which these patterns affect productivity in M. maximus.…”
Section: Qtls For Agronomic and Nutritional Traitsmentioning
confidence: 99%